National Honors 8th, and 9th grade choir. - The American Choral Directors Association. National Convention (1993 : San Antonio, Texas) (Greene, Iowa : Comprehensive Sound Services,5, 1993)
Resumen: ACDA Coro Nacional de Honor de octavo y ACDA Coro Nacional de Honor de noveno grado se presentaron en Texas, para la Convención Nacional ACDA en marzo en South Banquet Hall, San Antonio Convention. Center.
Contenido: Thou vistest the Earth / Maurice Greene--Kyrie (from mass in G) / Franz Schubert--The Lord is my shepherd / Allen Pote--Sanctus (from mass) / Leonard Bernstein--Palpahaugen / arr. Bradley Ellingboe--Jamaica market place / Larry Farrow--I hear american singing / Andre Thomas.
Título del envase : ACDA National Honors eight and ninth grade choir
Anton Armstrong, conductor
Keywords: MUSICA VOCAL; COROS (VOCES MIXTAS); CONCIERTOS